PENGARUH INDEPENDENSI DAN PROFESIONALISME, DALAM MENDETEKSI FRAUD PADA AUDITOR INTERNAL PROVINSI SULAWESI UTARA - Karamoy, Herman; Wokas, Heince R.N. (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2015)
This study to examine the influence of independency and professionalism, to detects fraud, at Accountant internal in Sulawesi Utara. This study used convenience sampling method, and the sampling of this research are 40 auditor internal in 4 Inspektorat of regency and city. The data were collected through questions survey methods. The analysis technique’s multiple regression. From the analyst there found partially professionalism, significant influence on detects fraud. While the independency partial no significant effect on detects fraud.